Prevalence of and factors associated with lactational mastitis in eastern and southern Africa: an exploratory analysis of community-based household surveys - Mariame O. Ouedraogo; Lenka Benova; Tom Smekens; Gezahegn G. Sinke; Abraha Hailu; Herbert B. Wanyonyi; Madalitso Tolani; Caristus Zumbe; Ibukun-Oluwa O. Abejirinde (BMC, 2022)
Abstract Background Lactational mastitis is an extremely painful and distressing inflammation of the breast, which can seriously disrupt breastfeeding. Most of the evidence on the frequency of this condition and its risk factors is from high-income countries. Thus, there is a crucial need for more information on lactational mastitis and its associated factors in Sub-Saharan Africa (SSA). Methods We used data from representative, community-based cross-sectional household surveys conducted in 2020 with 3,315 women from four countries (Ethiopia, Kenya, Malawi, and Tanzania) who reported ever-breastfeeding their last child born in the two years before the survey. Our measure of lactational mastitis was self-reported and defined using a combination of breast symptoms (breast redness and swelling) and flu-like symptoms (fever and chills) experienced during the breastfeeding period. We first estimated country-specific and pooled prevalence of self-reported lactational mastitis and examined mastitis-related breastfeeding discontinuation. Additionally, we examined factors associated with reporting mastitis in the pooled sample using bivariate and multivariable logistic regression accounting for clustering at the country level and post-stratification weights. Results The prevalence of self-reported lactational mastitis ranged from 3.1% in Ethiopia to 12.0% in Kenya. Close to 17.0% of women who experienced mastitis stopped breastfeeding because of mastitis. The adjusted odds of self-reported lactational mastitis were approximately two-fold higher among women who completed at least some primary school compared to women who had no formal education. Study participants who delivered by caesarean section had 1.46 times higher odds of reporting lactational mastitis than women with a vaginal birth. Despite wide confidence intervals, our models also indicate that young women (15 - 24 years) and women who practiced prelacteal feeding had higher odds of experiencing lactational mastitis than older women (25 + years) and women who did not give prelacteal feed to their newborns. Conclusions The prevalence of lactational mastitis in four countries of SSA might be somewhat lower than estimates reported from other settings. Further studies should explore the risk and protective factors for lactational mastitis in SSA contexts and address its negative consequences on breastfeeding.